Eavesdropping to Find Mates: The Function of Male Hearing for a Cicada-Hunting Parasitoid Fly, Emblemasoma erro (Diptera: Sarcophagidae). Issue 1 (5th July 2016) - Stucky, Brian J.
Abstract: Females of several species of dipteran parasitoids use long-range hearing to locate hosts for their offspring by eavesdropping on the acoustic mating calls of other insects. Males of these acoustic eavesdropping parasitoids also have physiologically functional ears, but so far, no adaptive function for male hearing has been discovered. I investigated the function of male hearing for the sarcophagid fly Emblemasoma erro Aldrich, an acoustic parasitoid of cicadas, by testing the hypothesis that both male and female E. erro use hearing to locate potential mates. I found that both male and nongravid female E. erro perform phonotaxis to the sounds of calling cicadas, that male flies engage in short-range, mate-finding behavior once they arrive at a sound source, and that encounters between females and males at a sound source can lead to copulation. Thus, cicada calling songs appear to serve as a mate-finding cue for both sexes of E. erro . Emblemasoma erro 's mate-finding behavior is compared to that of other sarcophagid flies, other acoustic parasitoids, and nonacoustic eavesdropping parasitoids.